Model Pembelajaran Dick and Carey Dan Implementasinya Dalam Pelajaran PAI - Masruroh, Durrotul (Global Education Journal, 2023)
This research aims to examine the Dick and Carey learning model and its implementation in the world of education, especially in Islamic religious education learning, using library research methodology. Based on the results of this research, the Dick and Carey learning model is very suitable for use in PAI learning in order to help students get optimal learning results. Most students think that PAI is just an entertainment lesson with no specific targets or emphasis, so students take it for granted. Therefore, teachers must be able to make students aware and motivate students about the importance of PAI lessons for us, religion, nation and state. The Dick and Carey learning model is a model that is very suitable for use in education, because it is a model that has clear steps and is focused on learning outcomes. It is systematic, orderly, there is a connection between one and the other so that students feel targeted and cared for, so students will continue to follow the steps and get optimal learning results.